Alternatively spliced tissue factor - van den Berg, Y. W.; Versteeg, H. H. (Hämostaseologie, 2010)
Full-length tissue factor (flTF) initiates coagulation, but also exerts non-hemostatic functions such as inflammation and angiogenesis through protease activated receptors (PARs). In 2003 a soluble variant of flTF was described which results from alternative splicing. Since its discovery the role of alternatively spliced tissue factor (asTF) in coagulation has been debated. asTF may have pro-coagulant properties but due to structural differences when compared to flTF, asTF coagulant function may be relatively low. Nevertheless, similar to flTF, asTF appears to have non-hemostatic properties; asTF expression in tumors correlates with increased tumor size, vessel number and poor survival in some cancer types, and drives tumor growth in animal models. Interestingly, unlike flTF, asTF does not promote angiogenesis through activating PARs but rather via integrin ligation. flTF is a critical determinant in cardiovascular disease but little is known about asTF in cardiovascular disease. asTF is produced by monocytes and macrophages, thus macrophage-derived asTF may contribute to atherosclerotic disease. In conclusion, unraveling asTF’s non-hemostatic properties may generate new insights in the pathophysiology and diagnostics of cancer and cardiovascular disease.
Keywords: Angiogenesis; cancer; cardiovascular disease; integrins